Code-Switching Practices in English Classrooms: A Sociolinguistic Study - Murniati Br Barus (JELT : Journal of English Education, Teaching and Literature, 2026)
This study investigates code-switching practices in English classrooms from a sociolinguistic perspective. It aims to identify the types of code-switching used by teachers and students, as well as to explore their functions in facilitating classroom interaction. The study employs a qualitative descriptive approach, with data collected through classroom observations and audio recordings of teaching and learning activities. The participants include one English teacher and a group of students in an EFL classroom setting. The findings reveal that code-switching occurs frequently during classroom interaction and serves important communicative and pedagogical purposes. Three types of code-switching were identified: inter-sentential switching, intra-sentential switching, and tag-switching. Among these, inter-sentential switching is the most dominant type, primarily used by the teacher to explain materials and ensure students’ comprehension. Intra-sentential switching is used by both teacher and students as a strategy to overcome vocabulary limitations, while tag-switching appears in maintaining interaction and checking understanding. Furthermore, the study shows that teachers use code-switching more frequently than students, reflecting their role in managing classroom communication. From a sociolinguistic perspective, code-switching is influenced by factors such as language proficiency, context, and communicative needs. In conclusion, code-switching is a valuable strategy in EFL classrooms that supports understanding and interaction. However, it should be used strategically to balance the use of the first language and the target language in order to optimize language learning outcomes.